Carta de Ira K. Wells a Charles Curtis - Wells, Ira K.; Curtis, Charles (My University, 1931)
Carta de presentación a Roberto H. Todd
Keywords: Puerto Rico--Política y gobierno.; Puerto Rico--Politics and government.